Research OF Complex Processes Based on Step-By-Step Modeling - Horbova, O. V; Murkovych, N. S (Science and Transport Progress, 2021)
Purpose. When solving practical problems that require the creation and further analysis of the model, an important criterion is the labour intensity of modeling. In this regard, the article is aimed at formalizing the modeling process and using the method of step-by-step modeling for the design of technological processes. This approach allows you to design processes and tasks according to the following stages: physical modeling, mathematical modeling, discrete computer modeling and simulation. Methodology. To solve the problem, a methodology of step-by-step modeling is used. The simulation involves 3 stages and uses the decomposition algorithm, i. e. considers the problem from global to detailed. At the first stage of this implementation, the necessary information is collected for the experiment. This information is presented in the form of statistics. In the second stage, further processing takes place, which is performed by checking the compliance of the input data and the process with the question of how this process should be performed. The last stage is the simulation of passages of this fragment, which is represented by a chain of transitions, obtaining statistics of time efficiency of this process, weaknesses of the process and the ability to compare the results obtained during modeling and in the real process, as well as the ability to predict future results and actions. Findings. The technique can be used to study complex technological processes in the enterprise. It allows modeling of complex processes to obtain information about the time efficiency of the technological operation, finding weaknesses in it and patterns in the occurrence of random events that may affect the operation. Using this approach can be very effective in the systems that require constant real-time monitoring, as this tool can be modified by adding sensor kits that will constantly send information to the system or equip an additional system that will provide ready-made information packets. Originality. The method of step-by-step modeling of representation has been improved, which consists in the simultaneous use of physical, mathematical and simulation modeling of complex processes with a set of stages of their implementation. Practical value. The proposed technique is designed for step-by-step modeling of the technological process with the subsequent construction of simulation programming.